Legal Organizing - Redefining the Function of Criminal Law - Abdullah, Firas (Journal of Legal Sciences, 2023)
This is a theatrical overview of the organizational approach regarding the definition of functions of criminal law and the nature of the criminal justice system. The research assumption is the following (organizational approach is the most important and effective instrument to achieve the goal of scientific-oriented law. The law should be defined by the terms of science, not by the terms of politics and relatively social norms. Through legally organized law social needs can be satisfied at the right time, and legislative intervention becomes more functional.